Teacher Conceptions Matter: Exploring the Relationships Between Mathematics Teachers’ Conceptions and Commitment in China - Lin, Wei; Yin, Hongbiao; Chai, Ching-Sing; Wang, Wenlan (The Asia-Pacific education researcher, 2020)
This study investigated the relationships between primary school mathematics teachers’ conceptions of mathematics, conceptions of teaching and learning, and their commitment in the context of mainland China. A total of 847 primary school mathematics teachers participated in a paper-based questionnaire survey. The results indicated that these teachers’ fragmented mathematics conceptions are positively associated with their traditional conceptions of teaching and learning while being negatively related to their constructivist conceptions of teaching and learning. In contrast, teachers’ cohesive mathematics conceptions are positively associated with both traditional and constructivist conceptions of teaching and learning. Meanwhile, only constructivist conceptions of teaching and learning are positively related to teacher commitment. These results imply that there is a need to enhance cohesive mathematics conceptions and reduce fragmented mathematics conceptions among Chinese primary school teachers in order to foster their constructivist teaching and commitment to students.